Julio Cuadros Caldas: un agrarista colombiano en la revolución mexicana - Palacios, Guillermo (El Colegio de México, A.C., 2000)
This work describes the participation of the Colombian thinker Julio Cuadros Caldas in the building and mobilization of peasant organizations in Puebla from 1920 to the beginning of 1933. Besides writing two volumes of memoirs and compiling a successful collection of agrarian laws and decrees for peasant groups. Cuadros Caldas founded and led the League of Agrarian Communities of Puebla, became personal informer of General Calles and Adalberto Tejeda and acted as agent for the Department of the Interior. He also played  important roles in the National Peasant League and in Puebla's ('"Emiliano Zapata") Social Confederation of Peasants, before being considered a "pernicious foreigner" and banished from Mexico in 1933.